Antibacterial Activity of Fermented and Non-Fermented Edel Cacao Bean Extract (Theobroma Cacao L.) Against Porphyromonas gingivalis - Mulki Nur Maajid; Rina Sutjiati; Rudi Joelijanto (Health Notions, 2021)
Porphyromonas gingivalis is considered the primary etiologic factor in periodontitis. The administration of antibiotics has so many adverse effects that alternative ingredients are needed with minimal side effects and as an agromedical-based innovation from herbal ingredients abundant in Jember district, namely extracts from cocoa beans. This study aimed to determine the antibacterial activity of fermented and unfermented cocoa bean extract (Theobroma cacao L.) with various concentrations against P. gingivalis. This research was conducted using fermented cocoa bean extract 1%, 2%, 3%, unfermented cocoa bean extract 1%,2%,3%, chlorhexidine as a positive control, aquadest as a negative control. Extracts were made using the Ultrasound-Assisted Extraction method, then tested for antibacterial using the disk diffusion method on Muller Hinton Agar media, four replications, 24 hours incubation, and measuring the inhibition zone with a caliper. The minimum inhibitory concentration of fermented cocoa bean extract was 3%, the size of the inhibition zone was 12.57 mm, the unfermented cocoa bean extract was 2%, the size of the inhibition zone was 11.67 mm. Test the difference using Kruskal walis, significance value 0.001. Antibacterial activity of cocoa bean extract (Theobroma cacao L.) unfermented Edel variety had more potent antibacterial activity against P. gingivalis than fermented one. The results of the Mann-Whitney test between samples showed that there were almost significant differences between the researched samples. Keywords: antibacterial; Porphyromonas gingivalis; cocoa beans